The Effect of Person–Job Fit to Job Involvement With Intrinsic Motivation as Intervening Variable - Ulan Dari, D; Gede Adi Permana, I B (KnE Social Sciences, 2018)
Background: Indonesia is incorporated in the ASEAN Economy Community (AEC). AEC’s impacts encourage companies to compete competitively to maintain their existence among competitors. Therefore, the company requires employees who have high levels of job involvement to be able to work effectively and efficiently. Job involvement is a positive attitude that encourages employees to contribute positively to the work. Purpose: To analyze the effect of person–job fit toward job involvement with intrinsic motivation as an intervening variable. Method: Data were collected with simple random sampling method, through observation and questionnaires that involved 131 employees from the central office at PT. Bank Pembangunan Daerah Jawa Timur Tbk’s Surabaya. Technical data testing used is SEM-PLS and Sobel test to study the effects of mediation. Result: Person–job fit influence is positively significant toward job involvement and intrinsic motivation. Intrinsic motivation proved to be a mediator in the relation between person–job fit and job involvement. Keywords: person–job fit, intrinsic motivation, job involvement